2016
DOI: 10.1111/pcn.12420
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in patients with schizophrenia: What is the next step?

Abstract: People with schizophrenia, who constitute approximately 0.3-1% of the general population, have a nearly 20% shorter life expectancy than the general population. The incidence of varied types of cancers in patients with schizophrenia is controversial. The majority of previous research has demonstrated that patients who have schizophrenia and cancer have early mortality compared to the general population with cancer. The causes of early mortality in patients with schizophrenia and cancer might be attributed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 70 publications
4
45
0
Order By: Relevance
“…In Taiwan, it has been found that these patients are more likely to die from physical illnesses such as myocardial infarction [32], strokes [33], diabetic mellitus [34], renal disease [35], and cancer [36]. Patients with schizophrenia in Taiwan have shorter lives than the general population when they have comorbid physical illnesses [31,37]. Although the Charlson Comorbidity Index was developed in a cohort of 559 medical patients [1] and not a population of patients with schizophrenia, we found that all the items of Charlson comorbidities were statistically associated with the mortality in our schizophrenic population, even after adjustment for demographic data and hospital level.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, it has been found that these patients are more likely to die from physical illnesses such as myocardial infarction [32], strokes [33], diabetic mellitus [34], renal disease [35], and cancer [36]. Patients with schizophrenia in Taiwan have shorter lives than the general population when they have comorbid physical illnesses [31,37]. Although the Charlson Comorbidity Index was developed in a cohort of 559 medical patients [1] and not a population of patients with schizophrenia, we found that all the items of Charlson comorbidities were statistically associated with the mortality in our schizophrenic population, even after adjustment for demographic data and hospital level.…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiological studies have demonstrated an inverse correlation between the two age-related diseases, cancer and neurodegenerative diseases [22][23][24], and this intriguing correlation was restricted to certain types of cancers and neurodegenerative diseases. Indeed, in the case of schizophrenia, varying degrees of risk for different types of cancers have been reported [284,285]. For instance, patients with schizophrenia have shown an increased, marginal, and decreased risk in colon, breast, and respiratory cancer, respectively [285].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Some studies have reported lower incidence rates suggesting biological mechanisms for protective effects. Chou et al reported that patients with schizophrenia have lower risk of some cancer types (Chou, Tsai, Su, & Lee, ; Chou, Tsai, Wu, & Shen, ). They have determined that patients with schizophrenia were less likely to develop cancer that individuals in the control group for every type of cancer except breast and cervival/uterine (Chou et al, , ).…”
Section: Discussionmentioning
confidence: 99%